Avaliação de um teste imunoenzimático indireto (ELISAi) na detecção de anticorpos anti Brucella abortus em novilhas imunizadas com vacina amostra B19 - Lossano, Diana Maria Lima (2020)
Bovine brucellosis is an infectious disease caused traditionally by the bacteria Brucella abortus. Diagnosis by serological methods and vaccination with the B. abortus B19 strain are the conventional and traditional forms of disease control. The standard